PENDIDIKAN ANTIKORUPSI DALAM KELUARGA: UPAYA MEMBANGUN KELUARGA SAKINAH - Aya Mamluah; Abdul Jalil (CENDEKIA: Jurnal Studi Keislaman, 2022)
Anti-corruption education in the family is ideally given by parents to their children from an early age. This is an initial provision so that children from an early age are accustomed to being honest, trustworthy, and clean-hearted without having to harm themselves and others. Therefore, there is a need for public awareness that education is not only carried out in schools and the responsibility is placed on the school alone. Rather, the roles and responsibilities of parents at home are much greater primarily by instilling character values in children and parenting styles. In this paper, it is explained and explained clearly both theoretically and practically. How is the correlation of family functions as the main basis for anti-corruption education in the family? What are the values given by parents and the methods used in character education in shaping anti-corruption education in the family? Through this paper, at least it provides a very interesting, easy-to-digest description, insight, education, and creativity about the importance of anti-corruption education in the family. So that you can practice it in your daily life.